Autobiographical memory deficits in Alzheimer's disease - Seidl, Ulrich; Lueken, Ulrike; Thomann, Philipp; Geider, Franz Josef; Schröder, Johannes (Journal of Alzheimer's disease, 2011)
Autobiographical memory comprises memories of one's own past that are characterized by a sense of subjective time and autonoetic awareness. Although autobiographical memory deficits are among the major complaints of patients with dementia, they have
Gesehen am 31.10.2022